Utilisation of physician reminders about smoking cessation improves patient outcome - Darr, Mohammed Qasim; Sheik, Sanaullah (International Journal Of Community Medicine And Public Health, 2023)
Background: Smoking is a major risk factor for cardiovascular disease and is prevalent amongst 18-64-year-olds (31.9%) in Qatar. Disease prevention through health promotion remains the cornerstone of physicians workload in primary care. Physician reminders (PR) be it electronic or physical can prompt doctors to offer smoking cessation services, hopefully reducing disease burden. The objective was to improve the identification of smokers and provision of smoking cessation services using a PR system in primary care. Methods: A prospective quality improvement project in a primary care health centre focusing on physician practices towards smokers. We analyzed physicians’ documentation post consultation looking for specific end points like use of the code “smoker” and referral rates to the smoking cessation clinic (SCC). Data was collected with and without use of a PR (used to identify smoker) and then compared for the difference in documentation and services offered. Results: The use of a physician reminder vastly improved the identification of smokers. This led to an increase in the use of the code ‘smoker’ by physicians by 43.5%. Documentation of smoking status and the provision of smoking cessation counselling both improved by 32.8%. There was an increase in referral rates (18.8%) to the SCC due to use of the physician reminder. There was a 7.9% rise in smokers attending the SCC. Conclusions: Using a physician reminder helped to improve the identification of smokers and patient provision of smoking cessation services such as referral to the SCC. Repeating the study using an electronic physician reminder incorporated within the EMR system would be beneficial given the findings from this study.